Closed Versus Open Supracondylar Fractures of the Humerus in Children: A Comparison of Clinical and Radiographic Presentation and Results. Issue 2 (February 2018) - Lewine, Eliza; Kim, Jaehon M.; Miller, Patricia E.; Waters, Peter M.; Mahan, Susan T.; Snyder, Brian; Hedequist, Daniel; Bae, Donald S.
Abstract : Background: The purpose of this investigation was to compare the presentation and postoperative results of children treated for open and closed, completely displaced type III supracondylar humerus fractures (SCFs). Methods: Thirty patients with open and 66 patients with closed, completely displaced type III SCFs were evaluated. Open fractures underwent irrigation and debridement, and all patients were treated by open or closed reduction and pin fixation. Medical records were reviewed to obtain demographic information as well as preoperative and postoperative clinical data regarding mechanism of injury, neurovascular status, associated injuries, postoperative range of motion, infections, and pain. Radiographs were evaluated to quantify displacement, Baumann's angle, humeral capitellar angle, position of the anterior humeral line, and adequacy of reduction. Outcomes were assessed using Flynn criteria. Mean clinical follow-up for the open and closed fracture groups was 8.9 and 5.7 months, respectively. Results: Both groups were similar with respect to age, sex distribution, weight and body mass index, laterality of involvement, and mechanism of injury. At presentation, 35% of closed SCFs and 23% of open SCFs presented with abnormal neurovascular status. There was a higher prevalence of diminished/absent pulses or distal limb ischemia in patients with open injuries (27%) compared with closed fractures (18%). Conversely, severely displaced closed fractures were more commonly associated with nerve injury/palsy at presentation (35%) than those with open fractures (23%). Spontaneous nerve recovery was seen in 87% within 3 to 6 months. Postoperative loss of reduction and malunion were more common in the closed fracture group. However, 84% of patients achieved good-to-excellent results by Flynn criteria, with no appreciable difference based upon open versus closed fractures. Conclusions: With timely wound and fracture treatment, the clinical and radiographic results of children treated for open SCFs is similar to those with closed type III injuries, with little increased risk for infection, malunion, or neurovascular compromise. Level of Evidence: Level III.